Soil and tree X-ray spectroscopy analysis of Brazilian tropical mangrove ecosystem - Alves, Elton Eduardo Novais (2018)
The present research has been performed in Concha D’Ostras Sustainable Development Reserve (CDSDR), Guarapari, Espírito Santo state, Southeast Brazil. We assess the mangrove soil and tree chemical composition and speciation by X-ray fluorescence (XRF) and absorption (XANES) spectroscopy techniques, collected in synchrotron radiation laboratories at Stanford University, California (SSRL), and CNPEM, Campinas-SP (LNLS). The present thesis was structured in four chapters, being three chapters have been wrote as scientific manuscripts. The Chapter I contains basic informations about the main research topics: 1) Mangrove ecosystems; 2) Spectroscopy techniques; and 3) Dendrochemistry studies. In the Chapter II, we compared the biogeochemistry of better preserved (P1) and contaminated (P2) tropical Brazilian mangrove soils in terms of elemental composition, pH and reduction- oxidation (redox) potential (Eh), and S speciation. XRF analysis showed unique depth-distributions of S, Fe, Cl, Ca, K, Ti, Cr, Br, Sr, and Zr in each area. Sulfur K-edge XANES spectroscopy showed that the mangrove location and conservation state influenced the soil S speciation. Pyrite (FeS 2 ) was the dominant S mineral (~50% of S) found in both soil profiles, and more abundant organic and elemental S (S-org and S 0 ) in profile P1 indicated greater microbiological activity in the better preserved mangrove site. A decrease in the proportion of SO 42- with depth in P1 following a decrease on Eh. However, in profile P2 we verified an increase in the SO 42- in deeper soil layers, indicating greater influx of from seawater. In essence, S speciation was directly influenced by seawater encroachment. In the Chapter III we evaluated the effect of tender X-ray radiation (2.4-2.6 keV) in the sulfur species present in environmental samples under cryo-temperature (115±5 K) to minimize the radiation-damage during S K-edge XANES analysis. We performed six sequential S K-edge XANES (2.4 to 2.6 keV) in pure standards (S 8 and FeSO 4 .7H 2 O), environmental samples (Pyrite, Frozen and Lyophilized Mangrove Soil), and a mixture of S 8 + Starch. Tender X-ray synchrotron radiation-damage resulted in the reduction of sulfur only in the carbon rich sample (S 8 + Starch). The cold finger at 115 K was effective in minimize the radiation-damage. Thus, it is recommended to use the cold finger during the S K-edge XANES data for those samples that are rich in organic carbon for environmental studies. Powder samples are recommended (as lyophilized soil) because they are simpler to mount, in order to obtain more homogenous sample, and avoid the analysis of gaseous sulfur species, which is important when the objective is to study only the solid state phases in the sample. In the Chapter IV we aimed to assess the Ca distribution and speciation into Avicennia mangrove tree, using μXRF and Ca K-edge μXANES analysis (5 μm beam size) combined with multivariate analysis during data process. Increment cores were extracted from the Avicennia mangrove at CDSDR and were analyzed by XRF and XANES techniques at SSRL. The Ca content was greater in internal part of wood (heartwood) than in the external part (sapwood) and showed a systematic distribution into tree-rings, being possible to use this data to identify “chemical-rings” in the sample. The PCA and cluster multivariate analysis showed that Ca species are distinct in the sapwood (more calcium oxalate and carbonate) and heartwood (more calcium sulfate), which can be related to a Ca role in the plant, as structural (heartwood) or a labile form (sapwood). This study showed that multivariate analysis of Ca speciation data and the Ca distribution in the tree-ring, using a microprobe X- ray spectroscopy, provide valuable information about chemical records in the mangrove tropical tree-rings.